2016
DOI: 10.17239/l1esll-2016.16.04.01
|View full text |Cite
|
Sign up to set email alerts
|

The impact of literature education on students' perceptions of self and others: Exploring personal and social learning experiences in relation to teacher approach

Abstract: The Dutch Institute for Curriculum Development argues that literature education is important for broadening students' personal, social and cultural horizons. Indeed, reading literary fiction may alter readers' self-and social perceptions, but little is known about whether adolescents gain such personal and social insights through reading in the secondary literature classroom, nor about how these perceived learning outcomes are related to their teachers' approaches to various aspects of literature teaching. Thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 42 publications
0
31
2
3
Order By: Relevance
“…According to previous research findings (e.g. Schrijvers et al, 2016), this is counterproductive to the teachers' efforts to increase the reading frequency among students. There is support for the idea that differentiated instructions, that is to say student-centered teaching, leads to students reading more (Beliaeva, 2009).…”
Section: Monitoringmentioning
confidence: 82%
See 3 more Smart Citations
“…According to previous research findings (e.g. Schrijvers et al, 2016), this is counterproductive to the teachers' efforts to increase the reading frequency among students. There is support for the idea that differentiated instructions, that is to say student-centered teaching, leads to students reading more (Beliaeva, 2009).…”
Section: Monitoringmentioning
confidence: 82%
“…Research shows that teachers' strategies and teaching approaches play a crucial role for learning outcomes (Yimwilai, 2015), and by constructing and focusing questions in a certain manner, teachers signpost the central aspects of a text to the students, and thus how a certain piece of work is expected to be approached (McCormick, 1994). Another factor that impacts on learning outcomes is the level of student-centeredness in the classroom (Mukhametshina & Akhmatova, 2015;Schrijvers et al, 2016). The new teacher role that Molloy (2002) speaks of springs from this anti-authoritative notion, and is one in which the teacher reads and discusses with the students to promote learning through social and intellectual encounters.…”
Section: The Swedish Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…Constructivist teaching seems to be institutionally hampered and a connection of the literary text to the perspective of young readers is not necessarily established. 2) That is unfortunate, since "literary fiction can be a vehicle for gaining insight into themselves and others" even when pupils are no 'bookworms' as Schrijvers, Janssen, Fialho and Rijlaarsdam (2016) premise in their insightful empirical inquiry. They showed that Dutch pupils reported experiences of personal and social learning, especially when their teachers' beliefs indicate constructivist notions like fostering classroom interaction and supporting autonomy.…”
Section: Overview On the Texts Of The Readermentioning
confidence: 99%